2022
DOI: 10.1136/lupus-2022-000836
|View full text |Cite
|
Sign up to set email alerts
|

Systemic blockade of proBDNF inhibited the expansion and altered the transcriptomic expression in CD3+B220+cells in MRL/lpr lupus mice

Abstract: ObjectivesThe overexpansion of CD3+B220+cells is the hallmark and main pathological mechanism of clinical manifestations of spontaneously developed MRL/lpr mice, which are primarily used as a mouse model of SLE. Our recent report demonstrated that blocking brain-derived neurotrophic factor precursor (proBDNF) suppressed the antibody-secreting cell differentiation and proliferation and inhibited the progression of SLE; however, the effect of proBDNF blockade on these CD3+B220+cells in MRL/lpr mice is unclear.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In vitro intervention with mAb-proB inhibited the CpGB-stimulated B cell differentiation and production of IgG and IgM in PBMCs from healthy volunteers and patients with SLE. Therefore, the proBDNF/p75 NTR signaling pathway promoted the proliferation of ASCs, which plays a pathogenic role in SLE and may be a potential therapeutic biological target for SLE (9,113). Our recent research indicated that mAb-proB inhibited the overexpansion of CD3 + B220 + cells and altered transcription levels related to cholesterol metabolism, cell cycle, and cell apoptosis, which may contribute to the attenuation of conditions of MRL/lpr lupus mice (10).…”
Section: Probdnf and Its Receptors In Slementioning
confidence: 99%
See 3 more Smart Citations
“…In vitro intervention with mAb-proB inhibited the CpGB-stimulated B cell differentiation and production of IgG and IgM in PBMCs from healthy volunteers and patients with SLE. Therefore, the proBDNF/p75 NTR signaling pathway promoted the proliferation of ASCs, which plays a pathogenic role in SLE and may be a potential therapeutic biological target for SLE (9,113). Our recent research indicated that mAb-proB inhibited the overexpansion of CD3 + B220 + cells and altered transcription levels related to cholesterol metabolism, cell cycle, and cell apoptosis, which may contribute to the attenuation of conditions of MRL/lpr lupus mice (10).…”
Section: Probdnf and Its Receptors In Slementioning
confidence: 99%
“…In animal experiments, proBDNF/p75 NTR signaling was significantly upregulated in B cells of spontaneous and induced lupus mice. The intraperitoneal administration of mAb-proB can alleviate the condition of spontaneous and induced lupus mice, reduce the proportion of ASCs and production of auto-antibody and proinflammatory cytokines, as well as delay kidney damage ( 9 , 10 ). Intraperitoneally administering pristane to induce lupus in B cell-specific p75 NTR knockout (CD19 cre p75 f/f ) mice showed that the knockout of B cell p75 NTR signaling can also alleviate the progression of SLE.…”
Section: Probdnf and Its Receptors In Slementioning
confidence: 99%
See 2 more Smart Citations